Anaerobic nitrate reduction divergently governs population expansion of the enteropathogen Vibrio cholerae. (December 2018) - Bueno, Emilio; Sit, Brandon; Waldor, Matthew; Cava, Felipe
Abstract To survive and proliferate in the absence of oxygen, many enteric pathogens can undergo anaerobic respiration within the host by using nitrate (NO3 − ) as an electron acceptor1, 2 . In these bacteria, NO3 − is typically reduced by a nitrate reductase to nitrite (NO2 − ), a toxic intermediate that is further reduced by a nitrite reductase3 . However, Vibrio cholerae, the intestinal pathogen that causes cholera, lacks a nitrite reductase, leading to NO2 − accumulation during nitrate reduction4 . Thus, V. cholerae is thought to be unable to undergo NO3 − -dependent anaerobic respiration4 . Here, we show that during hypoxic growth, NO3 − reduction in V. cholerae divergently affects bacterial fitness in a manner dependent on environmental pH. Remarkably, in alkaline conditions, V. cholerae can reduce NO3 − to support population growth. Conversely, in acidic conditions, accumulation of NO2 − from NO3 − reduction simultaneously limits population expansion and preserves cell viability by lowering fermentative acid production. Interestingly, other bacterial species such as Salmonella typhimurium, enterohaemorrhagic Escherichia coli (EHEC) and Citrobacter rodentium also reproduced this pH-dependent response, suggesting that this mechanism might be conserved within enteric pathogens. Our findings explain how a bacterial pathogen can use a single redox reaction to divergently regulate population expansion depending on the fluctuating environmental pH. During hypoxic growth in the gut, the levels of nitrate and nitrite affect V. cholerae in a pH-dependent manner. At high pH, the bacteria can reduce nitrate for growth, whereas at low pH, nitrite accumulates, limits proliferation and promotes cell viability.